A Hypothesis about Vahagn’s Mythological Image - Avagyan, Vachagan (Bulletin of Yerevan University B: Philology, 2021)
Relying on Agatangeghos and Movses Khorenatsi (both 5th c.), Vahagn, one of the great pre-Christian deities in Armenian mythology, the deity of war, with his mythological description, was combined with deities of both sun and thunderstorm. Due to its connection with the cosmic elements and the dragon fight, it was mostly perceived as the deity of thunderstorm, who, particularly in the Indo-European context, was identi39 fied with Indra and Heracles. The current paper, for the first time, circulates and examines from the folk studies the aspects, the motif of the lira playing attributed to Vahagn in the “History” of the 10th Century Historian Hovhannes Draskhanakertsi. It is shown that Vahagn, who is in some respects comparable to the image of the lira player Apollo, is similar to him with one more quality. Considering the similarity of the motives of Apollo’s and Vahagn’s lira playing, a possible hypothesis is being developed that in the ancient version of Vahagn’s legend he was a lira player who fought against dragons or monsters with his lira. Later, either because of the gradual darkening of the mythical memory or due to the development of people’s rational thinking, that motive has gradually weakened, faded but has not completely been forgotten and, as a mythic remnant, reached the 10th century and was passed from people to Hovhannes Draskhanakerttsi. It is not excluded either that, due to the ‘cultural dialogue and heritage’, the aforementioned legend on Apollo, perhaps only after Khorenatsi, was included in the local milieu orally and was associated with Vahagn’s name.